Association between serum 25-hydroxyvitamin D and global DNA methylation in visceral adipose tissue from colorectal cancer patients - Castellano-Castillo, Daniel; Morcillo, Sonsoles; Crujeiras, Ana B.; Sánchez-Alcoholado, Lidia; Clemente-Postigo, Mercedes; Torres, Esperanza; Tinahones, Francisco José; Macias-Gonzalez, Manuel (BMC cancer, 2019)
Background Visceral adipose tissue (VAT) has been identified as the essential fat depot for pathogenetic theories that associateobesity and colon cancer. LINE-1 hypomethylation has been mostly detected in tumor colon tissue, but less is known about the epigenetic pattern in surrounding tissues. The aim was to analyze for the first time the potential relationship between serum vitamin D, obesity and global methylation (LINE-1) in the visceral adipose tissue (VAT) from patients with and without colorectal cancer. Methods A total of 55 patients with colorectal cancer and 35 control subjects participated in the study. LINE-1 DNA methylation in VAT was measured by pyrosequencing. Serum 25(OH)D levels were determined by ELISA. Results Cancer patients had lower levels of LINE-1 methylation in VAT compared with the control group. In the subjects with colorectal cancer, LINE-1 DNA methylation levels were associated positively with vitamin D levels ( r = 0,463; p < 0.001) and negatively with BMI ( r = − 0.334, p = 0.01) and HOMA insulin resistance index ( r = − 0.348, p = 0.01). Serum vitamin D was the main variable explaining the LINE-1% variance in the cancer group (β = 0.460, p < 0.001). In a multivariate analysis, subjects with higher LINE-1 methylation values had lower risk of developing colorectal cancer (OR = 0.53; IC95% =0.28–0.99) compared with the control group. Conclusions We showed for the first time an association between LINE-1 DNA methylation in VAT and vitamin D levels in subjects with colorectal cancer, highlighting the importance of VAT from cancer patients, which could be modified epigenetically compared to healthy subjects.